Challenges for the diagnosis and treatment of malaria in low transmission settings in SanLorenzo, Esmeraldas, Ecuador (2018)
ABSTRACT: Background: Ecuador is on the verge of eliminating malaria according to the World Health Organization criteria. Nevertheless, active transmission foci still persist in the country, and these represent an important challenge for achieving the objectives set out. Diagnosis and treatment are a mainstay in the control and elimination of this disease. This study aimed to explore the barriers hindering the implementation of malaria diagnosis and treatment strategies in a focus of active transmission in the San Lorenzo canton, Ecuador.Methods: Using a convergent mixed methods design during 2017, the researchers assessed the physical and human resources of the services network at the primary level of care along with the quality assurance activities, patient access to healthcare services and perceptions regarding the care provided to patients with malaria.Results: The programme’s administrative transition from the National Service of Vector‑borne Diseases to the Minis‑try of Public Health is perceived from the interviewed participants to have weakened the diagnosis network estab‑lished in recent years. A mean of 6.4 ± 0.88 months was found for anti‑malarial medication shortage at the primary level of care. Likewise, there was high healthcare staff turnover (permanence, Me = 7 months; IQR = 5–16) and a defi‑cit of general knowledge on the disease among the entirety of healthcare staff, as only 29% of physicians were aware of the correct first‑line treatment for malaria by Plasmodium falciparum and Plasmodium vivax. It was evidenced that 95.7% of patients were hospitalized to receive anti‑malarial treatment. Both patients and healthcare staff considered the area to be difficult to reach due to its geography and the presence of groups outside the law. They also identified the lack of personnel and microscopy posts in this border area as the main barrier.Conclusion: The network of diagnostic services for malaria is weak in San Lorenzo, and socio‑economic, political and historical factors hinder the implementation of the universal malaria elimination strategy based on diagnosis and treatment.